Learning and library usage trends - a UTP case study - Ahmad Fadzil, Mohamad Hani, Dr; Wan Fatimah, Wan Ahmad, Dr (PETRONAS, 2010)
Organized by PETRONAS in collaboration with Pustaka Sumber Ilmu, 15th – 17th May 2005 at Nikko Hotel Kuala Lumpur, Malaysia.